THE ROLE OF CORPORATE SOCIAL RESPONSIBILITY (CSR) IN THE BAWASALO PLTU IN INCREASING THE ECONOMY OF SURROUNDING COMMUNITIES IN LAMPOKO VILLAGE, BALUSU DISTRICT, BARRU DISTRICT. - Lukman, Sri Hardiyanti; Muhammad, Mukmin; Ismail, Andi Muhammad Ishak (Meraja journal, 2022)
[Full Paper] to pdf Copyright (c) 2022 Meraja journal